Pinion Imagery in Chopin’s The Awakening - Dewan, Motikala Subba (Humanities and Social Sciences Journal, 2021)
This research explores the pinion imagery in Kate Chopin’s novel The Awakening. It tries to look at how the imagery of bird’s wings are used to describe the protagonist Edna Pontellier’s effort to break free from the existing mental and physical state in the anticipation of individual freedom. Being a mother of two children and wife of Léonce Pontellier, Edna has confined within the four walls of her house. However, she has been longing for true contentment and happiness in life. The aim of the research is to examine Edna’s struggle to achieve sexual and personal emancipation through the use of semiotics imagery of pinions. Edna’s attempt to escape her husband, children, and society manifest her strong feelings of eros and spreading wings for self-liberation and awakening however, her wings are broken and landed with injured heart leading her to thanatos.